2014
DOI: 10.3802/jgo.2014.25.3.229
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of lymphocele development in gynecologic cancers by the electrothermal bipolar vessel sealing device

Abstract: ObjectiveA number of new techniques have been developed to prevent lymphocele formation after pelvic lymphadenectomy in gynecologic cancers. We assessed whether the electrothermal bipolar vessel sealing device (EBVSD) could decrease the incidence of postoperative lymphocele secondary to pelvic lymphadenectomy.MethodsA total of 321 patients with gynecologic cancer underwent pelvic lymphadenectomy from 2005 to 2011. Pelvic lymphadenectomy without EBVSD was performed in 134 patients, and pelvic lymphadenectomy wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 33 publications
1
25
0
1
Order By: Relevance
“…Several surgical techniques and procedures have been reported for the prevention of lymphocele formation. For example, Tsuda et al [37] reported that the use of electrothermal bipolar vessel-sealing devices could reduce the risk of lymphocele formation after gynaecological surgery. Gallotta et al [38] demonstrated that the use of clip applicators was beneficial for preventing lymphocele formation.…”
Section: Discussionmentioning
confidence: 99%
“…Several surgical techniques and procedures have been reported for the prevention of lymphocele formation. For example, Tsuda et al [37] reported that the use of electrothermal bipolar vessel-sealing devices could reduce the risk of lymphocele formation after gynaecological surgery. Gallotta et al [38] demonstrated that the use of clip applicators was beneficial for preventing lymphocele formation.…”
Section: Discussionmentioning
confidence: 99%
“…Several successful attempts to reduce pelvic lymphocele in women with gynecological cancer by using novel vessels sealing devices, such as Ligasure® [13], Ultracisions® [14] or Ligaclip [9] have been described in the literature. In addition, TachoSil® has also been proposed as a possible strategy to prevent postoperative lymphocele [15,16,17].…”
Section: Discussionmentioning
confidence: 99%
“…But it is often accompanied by complications, such as hemorrhage, hematoma, and lymphocele [52,53]. Of these, lymphocele is one of the most common postoperative complications in that it leads to the occurrence of VTE by venous compression [54,55]. According to a review of the literature, VTE occurred after lymphadectomy at an estimated incidence of 0.8-25% [56][57][58].…”
Section: Discussionmentioning
confidence: 99%